Tandem Mass Spectrometry of Sphingolipids: Application in Metabolic Studies and Diagnosis of Inherited Disorders of Sphingolipid Metabolism - Kuchař, Ladislav; Asfaw, Befekadu; Ledvinová, Jana (IntechOpen, 2012)
None